Stage IIB-IVA cervix carcinoma in elderly patients treated with radiation therapy: a longitudinal cohort study by propensity score matching analysis - Huafeng Shou; Qiuyan Wan; Hong'en Xu; Lei Shi; Tao Song (BMC, 2023)
Abstract Objective We aimed to evaluate the treatment modality and prognostic impact of the age at diagnosis on stage IIB-IVA cervix carcinoma (CC) patients who received radiotherapy (RT).The evaluation was performed using the Surveillance, Epidemiology, and End Results (SEER) database. Patients and methods From the SEER database, we included the patients with a histopathological diagnosis of CC between 2004 and 2016. Subsequently, we compared the treatment outcomes between patients aged ≥ 65 years (OG) and < 65 years (YG) by propensity score matching (PSM) analysis and Cox proportional hazard regression models. Results The data of 5,705 CC patients were obtained from the SEER database. We observed that the OG patients were significantly less likely to receive chemotherapy, brachytherapy, or combination treatment compared to the YG (P < 0.001). Further, the advanced age at diagnosis was an independent prognostic factor associated with decreasing overall survival (OS) before and after PSM. Even in the subgroup analysis of patients who received trimodal therapy, an advanced age had a significant negative impact on OS compared to their younger counterparts. Conclusion Advanced age is associated with less aggressive treatment regimens and is independently associated with impaired OS for stage IIB-IVA CC patients who received RT. Hence, future studies should incorporate geriatric assessment into clinical decision-making to select appropriate and effective treatment strategies for elderly CC patients.